SUBSTANTIATION OF TECHNOLOGY AND QUALITY EVALUATION OF SOYA-MUSHROOM FUNCTIONAL FOODS - Skripko O.V.; Litvinenko O.V.; Pokotilo O.V. (Техника и технология пищевых производств)
Production of foods for functional nutrition is one of the most perspective directions of development of food industry now. The goal of our research is scientific substantiation of technological approaches to obtaining combined functional foods prepared with the use of plant raw materials which grow in the Far East such as soya and mushrooms. The research results enable us to develop the technology of preparation of functional foods on the basis of compatibility and complementarities of the component composition of raw material in the form of pastes and concentrates, as well as to get mathematical models of preparation process of soya-mushroom foods. By means of these models parameters and modes of preparation of combined disperse systems have been justified: mass fraction of ascorbic acid solution is 14.7%, concentration of ascorbic acid is 6.2% and duration of clot formation is 4.8 minutes, while the optimum temperature for clot formation is 66°С; initial moisture of clot is 41.4%, drying temperature of granules is 66°С, drying time of granules is 64 minutes, thus, hardness of the obtained granules is provided within 91%. The research has shown that consumption of the developed foods raise the possibility to meet daily requirements of people in vitamins С, Е, РР, minerals - potassium, phosphorus, as well as dietary fibers that confirms their functional properties. The normative-technical documentation in the form of the organization standard and technological instructions for the production of soya-mushroom paste and concentrate has been developed on the basis of obtained results. New foods can be produced at food-service enterprises and food-concentrates producing plants.